Inhibition of protein tyrosine phosphatase (PTP1B) and α-glucosidase by geranylated flavonoids from Paulownia tomentosa - Yeong Hun Song; Zia Uddin; Young Min Jin; Zuopeng Li; Marcus John Curtis-Long; Kwang Dong Kim; Jung Keun Cho; Ki Hun Park (Taylor & Francis Group, 2017)
Protein tyrosine phosphatase 1B (PTP1B) and α-glucosidase are important targets to treat obesity and diabetes, due to their deep correlation with insulin and leptin signalling, and glucose regulation. The methanol extract of Paulownia tomentosa fruits showed potent inhibition against both enzymes. Purification of this extract led to eight geranylated flavonoids (1-8) displaying dual inhibition of PTP1B and α-glucosidase. The isolated compounds were identified as flavanones (1-5) and dihydroflavonols (6-8). Inhibitory potencies of these compounds varied accordingly, but most of the compounds were highly effective against PTP1B (IC50 = 1.9-8.2 μM) than α-glucosidase (IC50 = 2.2-78.9 μM). Mimulone (1) was the most effective against PTP1B with IC50 = 1.9 μM, whereas 6-geranyl-3,3',5,5',7-pentahydroxy-4'-methoxyflavane (8) displayed potent inhibition against α-glucosidase (IC50 = 2.2 μM). All inhibitors showed mixed type Ι inhibition toward PTP1B, and were noncompetitive inhibitors of α-glucosidase. This mixed type behavior against PTP1B was fully demonstrated by showing a decrease in Vmax, an increase of Km, and Kik/Kiv ratio ranging between 2.66 and 3.69.